E ENVIRONMENTALLY SUSTAINABLE BUSINESS MODEL FOR CULINARY MSME’S IN EAST JAVA COASTAL TOURISM AREAS - Irra Chrisyanti Dewi; Fabiola Leoparjo; Kristian Agung Nugraha (RADJA PUBLIKA, 2026)
This study focuses on the development of an eco-friendly business model for culinary MSMEs in the coastal tourism area of ​​East Java, Indonesia. The rapid growth of culinary MSMEs in this area has resulted in significant environmental challenges, including increased waste and unsustainable resource use. This study aims to develop a model that integrates environmental sustainability with economic growth in the culinary sector, adopting the triple bottom line approach, which encompasses economic, social, and environmental factors. This qualitative study used a case study design. Data were collected from in-depth interviews, observation, and documentation. The analysis focused on eco-friendly business practices, supporting and inhibiting factors, and an eco-friendly business model to improve the profitability and environmental performance of culinary MSMEs and contribute to sustainable tourism practices. This study encourages policymakers, business owners, and other stakeholders to promote an eco-friendly culinary industry in the coastal tourism area of ​​East Java.